Effect of Midazolam, Fentanyl and I.V Lidocaine to Decrease The Stress Response of Laryngoscopy and ETT Intubation - Alkhashab, Radhwan H.; Husain, Saad A.; Ali, Ali J. (Scientific Journal of Medical Research, 2019)
Objectives: The aim of the study to evaluate the role of fentanyl, midazolam and lidocaine in attenuation the hemodynamic response (stress response) of heart rate and blood pressure at induction of anesthesia, laryngoscopy and endotracheal intubation. Endotracheal intubation always associated with marked increases in heart rate and systemic blood pressure1. Marked increases in hemodynamic parameters occur after direct laryngoscopy and endotracheal intubation in patients with chronic hypertension. Methods: A double blind study was done in Aljamhory teaching hospital, Mosul city, Iraq, from december 2012 - May 2014. All the patients were in the age of 40 - 70 years and ASA II were all hypertensive and they were on routine antihypertensive agents. In this study a 87 patients, males and females prepared for surgery needed endotracheal intubation, group A 44 patients underwent pre medication with fentanyl, midazolam and lidocaine and group B 43 patients pre medicated with fentanyl and midazolam. Results: The average age in group A is 52.27 years and in group B is 50.46, there was no significant difference in the sex, weight or age distribution of patients. There was no significant difference statistically between the two groups (P ? 0.05) in heart rate and blood pressure in pre induction , after induction and after endotracheal intubation. Conclusion: Because of stress response due to surgery and anesthesia, most of the patients’ needs anxiolytics, sedatives and pain killers as a pre medication, were as every patient complaining from hypertension (ASA II) needs anxiolytic, sedative and narcotic (pain killer) to overcomes the fluctuation in HR and BP.